2010
DOI: 10.1021/jf1029509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by High-Performance Liquid Chromatography Diode Array Detection Mass Spectrometry of Phenolic Compounds in Fruit of Eucalyptus globulus Cultivated in Algeria

Abstract: A method based on high-performance liquid chromatography coupled with diode array detection and electrospray ionization mass spectrometry (HPLC-DAD-ESI-MS) following fractionation by chromatography on a Sephadex LH-20 column has been developed to determine the phenolic composition of fruit of Eucalyptus globulus growing in Algeria. The presence of 18 gallotannins, 26 ellagitannins, and 2 flavonols was established. Tentative identification is provided for these compounds on the basis of UV-visible spectra and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
67
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 44 publications
9
67
0
3
Order By: Relevance
“…Analysis of chromatographic proWle did not showed signals at 520 nm, suggesting the absence of anthocyanins in the extract [23]. It was also ruled out the presence of ellagic acid by the absence of maximum absorbance in 250 and 365 nm (24). The chromatogram (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Analysis of chromatographic proWle did not showed signals at 520 nm, suggesting the absence of anthocyanins in the extract [23]. It was also ruled out the presence of ellagic acid by the absence of maximum absorbance in 250 and 365 nm (24). The chromatogram (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…1) showed two major peaks (A and B) close to the retention times of 10 and 20 min, respectively, which can be assumed as belonging to the group of phenolic acids and their derivatives. The peaks A and B showed maximal absorbance in range from 265 to 280 nm which matches with that of gallic acid ( max » 275 nm) [24], as well as the UV spectra of peak A and gallic acid standard were superimposed, conWrming its identiWcation. HPLC-DAD showed that the peak B is a gallic acid derivative.…”
Section: Resultsmentioning
confidence: 99%
“…Retention time (tR) from RP-HPLC analysis. b Tentative identifications were achieved using RT mapping and fragmentation-pattern comparison to those of commercial standards as well as compounds previously reported in plant material byBoulekbache-Makhlouf et al (2010) and pecans by de la Rosa et al…”
mentioning
confidence: 99%
“…Eucalyptus is one of the world's important and most widely planted genera [2] . It is a tall, evergreen tree, native to Australia and Tasmania, successfully introduced worldwide, now extensively planted in many other countries [3] .It was introduced in Algeria in 1854 by Ramel [4] . Eucalyptus species are well known as medicinal plants because of their biological and pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%